Response of plankton community respiration under variable simulated upwelling events - Baños, Isabel; Arístegui, Javier; Benavides, Mar; Gómez-Letona, Markel; Montero, María F.; Ortiz, Joaquín; Schulz, Kai G.; Ludwig, Andrea; Riebesell, Ulf (Frontiers in Marine Science, 2022)
Climate change is expected to alter the intensity and frequency of upwelling in high productive coastal regions, thus impacting nutrient fluxes, primary productivity and consequently carbon cycling. However, it is unknown how these changes will impact the planktonic (phytoplankton and bacteria) community structure, which affects community respiration (CR) and hence the carbon available for sequestration or transfer to upper trophic levels. Here we present results from a 37-day mesocosm experiment where we examined the response of CR to nutrient additions by simulating upwelling events at different intensities (low, medium, high and extreme) and modes (singular and recurring additions). We also analysed the potential contribution of different plankton size classes and functional groups to CR. The trend in accumulated CR with respect to nutrient fertilisation (total nitrogen added during the experiment) was linear in the two modes. Microplankton (mostly diatoms) and nanoplankton (small flagellates) dominated under extreme upwelling intensities and high CR in both singular and recurring upwelling modes, explaining >65% of the observed variability in CR. In contrast, prokaryotic picoplankton (heterotrophic bacteria and autotrophic cyanobacteria) explained <43% of the variance in CR under the rest of the upwelling intensities and modes tested. Changes in planktonic community structure, while modulating CR variability, would regulate the metabolic balance of the ecosystem, shifting it towards net-heterotrophy when the community is dominated by small heterotrophs and to net-autotrophy when large autotrophs prevail; although depending on the mode in which nutrients are supplied to the system. This shift in the dominance of planktonic organism will hence affect not only CR but also carbon sequestration in upwelling regions